Physiological, biochemical, and molecular aspects of soybean resistance against Phakopsora pachyrhizi infection potentiated by some induced resistance stimuli - Rodrigues, Flávia Caroline Torres (2022)
Asian soybean rust (ASR), caused by Phakopsora pachyrhizi, is a destructive disease affecting soybean production and has been controlled mainly by using different fungicide molecules. The finding of new environmentally-friendly control strategies to minimize fungicide sprays must be prioritized. In this scenario, induced resistance using an array of abiotic or biotic inducers of resistance becomes a very promising alternative. The study investigated the potential of using azelaic acid (AzA), hexanoic acid (HxA) and Mantus ® (copper (20%) and polyphenolic (10%)) to reduce SR symptoms by boosting defense responses. In the first study, the factors studied were plants sprayed with water (control), acibenzolar-S-methyl (ASM), AzA or HxA that were non-inoculated or inoculated with P. pachyrhizi. Both AzA and Hxa significantly inhibited urediniospores germination in vitro. The area under disease progress curve significantly decreased by 95, 93, 92, 82, and 92% for ASM, HxA 5 mM, HxA 20 mM, AzA 0.1 mM, and AzA 1 mM, respectively, compared to control treatment. Hyphae of P. pachyrhizi colonized less abundantly the leaflet tissues of plants sprayed with ASM, HxA (20 mM), and AzA (1 mM) in comparison to water-sprayed plants. Infected and AzA and HxA-sprayed plants showed less impairment on their photos ynthesis and a more robust antioxidative metabolism in contrast to infected and water-sprayed plants. In general, host genes associated with general defense as well as with systemic acquired resistance or induced systemic resistance were strongly up- regulated for infected plants sprayed with AzA, ASM and HxA in comparison to water-sprayed plants. Interestingly, most of the genes were expressed earlier for infected and HxA-sprayed plants than for infected and AzA-sprayed plants, and more expressively in comparison to infected and ASM-sprayed plants. In the second study, the factors studied were plants sprayed with water or Mantus ® (referred to as induced resistance (IR) stimulus thereafter) that were non-inoculated or inoculated with P. pachyrhizi. Urediniospores germination was reduced by 97% by the IR stimulus in vitro. The SR severity and area under disease progress curve decreased by 68 and 35%, respectively, for IR stimulus-sprayed plants compared to water- sprayed plants. Defense-related genes were up-regulated for IR stimulus-sprayed plants compared to water-sprayed plants during the infection process of P. pachyrhizi. Infected and IR stimulus-sprayed plants showed less impairment in their photosynthesis and a more robust antioxidative metabolism in contrast to infected and water-sprayed plants. The results reported here highlight the potential of using AzA and HxA and this IR stimulus for SR management considering its fungistatic effect against urediniospores and by priming soybean resistance more efficiently to cope against P. pachyrhizi infection. Keywords: Glycine max. Disease management. Induced resistance. Plant defense mechanisms. Photosynthesis. Rust. Reactive oxygen species.